Mucosal Healing and Clinical Efficacy of Adalimumab in Small Intestinal Crohn’s Disease (SIMCHA Study): Final Results From a Prospective, Open-Label, Single-Arm Study - Wetwittayakhlang, Panu; Verdon, Christine; Starr, Michael; Hahn, Gustavo Drügg; Golovics, Petra A.; Bessissow, Talat; Afif, Waqqas; Wild, Gary; Bitton, Alain; Lakatos, Peter L. (Turkish Journal of Gastroenterology, 2023)
Background: Endoscopic healing is a key treatment target in inflammatory bowel disease; few data are available on the clinical and endoscopic efficacy of biological therapy in upper gastrointestinal Crohn’s disease. This study aimed to investigate small bowel mucosal healing and clinical efficacy of adalimumab therapy by video capsule endoscopy in patients with endoscopically active upper gastrointestinal Crohn’s disease. Methods: This prospective, open-label, single-arm study included Crohn’s disease patients with moderate–severe endoscopic proximal small bowel involvement, defined by a Lewis score >790. Patients were treated with adalimumab monotherapy for 24 weeks. Co-primary outcomes were endoscopic healing, defined as Lewis score <350, and endoscopic response, defined as >50% decrease in Lewis score. Secondary outcomes included clinical (Harvey–Bradshaw index <4) and biomarker remission (fecal calprotectin <250 μg/g, and C-reactive protein <5 mg/L). Results: A total of 59 Crohn’s disease patients were screened; 17 patients have met eligibility criteria and were enrolled. Endoscopic healing was observed in 8 patients (47.1%) and endoscopic response in additional 5 patients (29.4%) at 24 weeks. Median Lewis score was significantly decreased compared to baseline (1912 vs. 337, P = .0005). Eleven of 13 patients (84.6%) with clinical activity achieved clinical remission (baseline: 13/17 vs. week 24: 2/17, P < .0001). Nine of 10 patients with elevated C-reactive protein achieved normal C-reactive protein after treatment and the median C-reactive protein significantly decreased from 7.4 to 1.6 mg/L, P = .032. In contrast, no change was observed in fecal calprotectin pre- and posttreatment. Conclusions: Adalimumab induced endoscopic healing and clinical remission in patients with active small bowel Crohn’s disease, with approximately half of the patients achieving endoscopic healing.